Groundwater Treatment in Rungkut Sub-District, Surabaya - Setyo Budi Kurniawan; Ipung Fitri Purwanti; Bieby Voijant Tangahu; Harmin Sulistyaning Titah; Sarwoko Mangkoedihardjo (Institut Teknologi Sepuluh Nopember, 2017)
Results of Environment agency laboratory test show the Surabaya’s clean water which still meet quality standards by the year 2008 reached 97.5% and decreased to 58.2% in 2009. Rungkut is one of the sub-districts in Surabaya where people fulfill their daily water by using well water or ground water. Nowadays, people feel their well water is not feasible in use for everyday needs anymore. This was due to the decreased quality of well water because the contamination of organic matter. These community services activities try to help Rungkut Sub-District people in meeting their water needs. Efforts will be preceded by a hearing, sampling groundwater at some point, and test the quality of the groundwater. The results of groundwater quality test obtained will be used to create a water treatment unit which can be operated simply by the community. Based on the groundwater quality test obtained, the pilot scale unit of groundwater treatment designed and installed using multiple tray aerator and carbon active filter combination. Multiple tray aerator installed for 3 steps of aeration and the carbon active filter contains 60% (volume by volume) carbon active media.